Comparison of Least Significant Bit, Pixel Value Differencing, and Modulus Function on Steganography to Measure Image Quality, Storage Capacity, and Robustness. Issue 1 (January 2021) - Darwis, D; Pamungkas, N B; Wamiliana,
Abstract: Information security is an important aspect of information. The importance of the value of information in every aspect can result in attempts to transfer access or theft of data and information by unauthorized parties. One technique for securing data and information is by applying the digital image steganography technique. Many methods can be used in steganography, some of which are Least Significant Bit (LSB), Pixel Value Differencing (PVD), and Modulus Function (MF). Good steganography must produce a stego-image with an image quality that is not different from the original image or what is called a cover image and has the storage capacity to store confidential data and is resistant to robustness. The purpose of this study was to compare the LSB, MF, and PVD methods to serve as alternatives to the use of steganography techniques. The results of this study indicate that the LSB method has the best image quality compared to the MF and PVD methods. For storage capacity, the PVD algorithm has a better capacity than the LSB and MF methods. Meanwhile, the robustness of the LSB, PVD, and MF methods has resistance to cropping with a percentage of 10% at the bottom of the stego-image.